DESIGN OF A 16-STORY HOTEL BUILDING IN SOUTHEAST LOUISIANA, USA - Akhmedova, Akzhan; Nagimetov, Daulet; Togay, Amina; Toleubekov, Bauyrzhan; Muldabekova, Dana; Tanzhanova, Luiza (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This capstone report presents the design, implementation, and evaluation of Design of 16-story Hotel Building in South Louisiana, USA , a project aimed at the design a building considering its environmental wastes management, construction management, structural design and geotechnical design. The primary objectives of this project were to get familiarized with design of the above listed criteria. The methodology involved designing structural elements using ACI 7-10 code. Overall, this report contributes to the field of Civil and Environmental Engineering by offering the design of 16-story hotel building.
Keywords: Type of access: Open Access; civil engineering; design; construction management; structural engineering